Bio-adhesion to thin films in relation to cleaning - Greenberg, Charles B.; Steffek, Cory (Thin solid films, 2005)
The science and technology of thin films is so well developed at this time that it has become commonplace to think about them, relative to bulk counterparts, in terms of optical, mechanical, magnetic and electrical properties imparted to otherwise passive or unoptimized substrates. There are very good reasons, scientific and practical, to also think of thin films in respect to microbial adhesion. The interfacial chemistry has broad scientific implications, and practical consequences relate, at least, to problems of surface cleaning, and threat reduction as a part of that. We only introduce the bio-adhesion-to-film subject here.